2000
DOI: 10.1111/1467-9450.00202
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic symptomatology in children exposed to war

Abstract: This study examines affective and behavioral symptomatology in two groups of school-age children who were traumatized to different degrees during the war in Croatia (N = 1034). Six self-reported questionnaires were used to assess the following: number and type of war experiences, PTSD symptoms, anxiety, depression, psychosomatic symptoms, and psychosocial adaptation. Canonical discriminant analysis yielded a significant discriminant function that indicates moderate differentiation between the two groups of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 19 publications
3
36
0
Order By: Relevance
“…Girls reported higher levels of distress compared to boys, and older youth had more symptoms compared to younger ones. The higher levels of distress found among girls were expected, since former studies have indicated that girls tend to be more vulnerable to stressful political events (Klingman 1992;Kuterovac et al 1994;Vizek-Vidovic et al 2000;Durakovic-Belko et al 2003). This may be the result of greater social approval for girls to reveal and admit weaknesses and distress (Gavranidou and Rosner 2003;Dindia and Allen 1992).…”
Section: Discussionmentioning
confidence: 75%
“…Girls reported higher levels of distress compared to boys, and older youth had more symptoms compared to younger ones. The higher levels of distress found among girls were expected, since former studies have indicated that girls tend to be more vulnerable to stressful political events (Klingman 1992;Kuterovac et al 1994;Vizek-Vidovic et al 2000;Durakovic-Belko et al 2003). This may be the result of greater social approval for girls to reveal and admit weaknesses and distress (Gavranidou and Rosner 2003;Dindia and Allen 1992).…”
Section: Discussionmentioning
confidence: 75%
“…Studies of refugee children conducted outside the war zone are most common [14][15][16][17][18][19][20][21]. However, assessments have also been conducted in war zones including Bosnia [22][23][24], Kosovo [25], Croatia [26], and Iraq [27]. Two studies have addressed the problems of Palestinian children [28,29]; however, only one investigation provided systematic data about African children, in which approximately 3000 children were assessed 13 months after the 1994 genocide in Rwanda [30•].…”
Section: Warmentioning
confidence: 99%
“…This suggests that some depression may be secondary to persistent PTSD symptoms and may contribute to the onset and severity of secondary depression [5]. Disturbance in conscience functioning [7], anxiety, problems with peer relationships [38••], and psychosomatic complaints have been described [26] in association with posttraumatic stress symptoms.…”
Section: Other Post-disaster Reactions and Comorbiditymentioning
confidence: 99%
“…Children exposed to disasters are considered a particularly vulnerable group for developing psychiatric disorders [8][9][10][11]. In particular, several studies have been reported in youth who have experienced natural disasters; negative outcomes, such as anxiety and depression [12,13]; and posttraumatic stress disorder (PTSD) symptoms [14,15], which include re-experiencing, avoidance, emotional numbing, and hyperarousal [16].…”
Section: Introductionmentioning
confidence: 99%